Structure-function relationships in the stem cell's mechanical world B: emergent anisotropy of the cytoskeleton correlates to volume and shape changing stress exposure - Chang, Hana; Knothe Tate, Melissa L (Molecular & cellular biomechanics, 2011)
In the preceding study (Part A), we showed that prescribed seeding conditions as well as seeding density can be used to subject multipotent stem cells (MSCs) to volume changing stresses and that changes in volume of the cell are associated with changes in shape, but not volume, of the cell nucleus. In the current study, we aim to control the mechanical milieu of live cells using these prescribed seeding conditions concomitant to delivery of shape changing stresses via fluid flow, while observing adaptation of the cytoskeleton, a major cellular transducer that modulates cell shape, stiffness and remodeling. We hypothesize that the spatiotemporal organization of tubulin and actin elements of the cytoskeleton changes in response to volume and shape changing stresses emulating those during development, prior to the first beating of the heart or twitching of muscle. Our approach was to quantify the change over baseline in spatiotemporal distribution of actin and tubulin in live C3H/10T1/2 model stem cells subjected to volume changing stresses induced by seeding at density as well as low magnitude, short duration, shape changing (shear) stresses induced by fluid flow (0.5 or 1.0 dyne/cm2 for 30/60/90 minutes). Upon exposure to fluid flow, both tubulin thickness (height) and concentration (fluorescence intensity) change significantly over baseline, as a function of proximity to neighboring cells (density) and the substrate (apical-basal height). Given our recently published studies showing amplification of stress gradients (flow velocity) with increasing distance to nearest neighbors and the substrate, i.e. with decreasing density and toward the apical side of the cell, tubulin adaptation appears to depend significantly on the magnitude of the stress to which the cell is exposed locally. In contrast, adaptation of actin to the changing mechanical milieu is more global, exhibiting less significant differences attributable to nearest neighbors or boundaries than differences attributable to magnitude of the stress to which the cell is exposed globally (0.5 versus 1.0 dyne/cm2). Furthermore, changes in the actin cytoskeletal distribution correlate positively with one pre-mesenchymal condensation marker (Msx2) and negatively with early markers of chondrogenesis (ColIIaI alone, indicative of pre-hypertrophic chondrogenesis) and osteogenesis (Runx2). Changes in the tubulin cytoskeletal distribution correlate positively with a marker of pericondensation (Sox9 alone), negatively with chondrogenesis (ColIIaI) and positively with adipogenesis (Ppar-gamma 2). Taken as a whole, exposure of MSCs to volume and shape changing stresses results in emergent anisotropy of cytoskeletal architecture (structure), which relate to emergent cell fate (function).